Conversion of glucose into platform chemicals using aluminophosphates (SAPO-5 and MeAPO-5) in [BMIM]Cl ionic liquid - L. Ayele; G. Dadi; W. Mamo; Y. Chebude; I. Diaz (Bulletin of the Chemical Society of Ethiopia, 2014)
The conversion of glucose into platform chemicals such as 5-hydroxymethylfurfural, levulinic acid and formic acid has been investigated using two aluminophosphate based zeotypes (SAPO-5 and MeAPO-5) catalysts in 1-butyl-3-methylimidazolium chloride [BMIM]Cl ionic liquid as a reaction medium. The silico aluminophosphates (SAPO-5) and metal aluminophosphates (MeAPO-5) were designed and chosen for their tunable amount and strength of acid sites. The dehydration of glucose using each catalyst gave more than 90% glucose conversion. Among all the catalysts tested, the most hydrophilic SAPO-5 (1.5T) results in a better 5-HMF yield of 8% at 100 °C and 6 h reaction time. Contrary to this, the more hydrophobic SAPO-5 gives higher yield of levulinic acid and formic acid and no 5-HMF yield at this particular reaction time. In general, despite the higher glucose conversion attained by these aluminophosphate based catalysts, the lower yield obtained by these materials can be attributed to the type of acidity and the incompatibility of the pore diameter of the AFI channels of the catalysts and the desired products. DOI: http://dx.doi.org/10.4314/bcse.v28i1.6